BUKU ILUSTRASI TENTANG “PERJALANAN HIDUP SEBAGAI ANAK TULI” - Refina Gunawan; Carolus Astabrata; Irwan Harnoko (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract : Deaf Children are children who have hearing deficiencies so they cannot hear sounds perfectly. There are two types, namely mild and severe deafness. Mild deafness is a child who can hear and differentiate the sounds of words and animals and also uses assistive devices, but the drawback is that not everyone can hear clear sounds. Meanwhile, severe deafness means only being able to hear sounds, for example whether there is a sound or not, and not being able to differentiate between the sounds of words or animals either. Hearing Aids for deaf people are devices that help people hear sounds around them. Illustration is processing or creative work that provides image or visuals that are always used to tell or illustrate something creative, such as image illustrators who use manual or digital tools. The aim is to clarify the plot of the story and convey the contents of the story from deaf children so that readers can understand when reading. Illustrations help deaf people by telling stories of deaf children struggling to become successful and also deaf children having the motivation to provide encouragement to the deaf community.